KAJIAN TEOLOGIS TERHADAP BUDAYA BELIS DALAM PERKAWINAN MASYARAKAT SUMBA - Yunus Selan; Apliana Beili; Sri Dwi Harti (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2023)
This study discusses the theological analysis of giving belis in marriages for the people of Sumba. This culture or custom has been passed down from generation to generation and always intersects with church marriage. There are many different responses to belis in Sumba community marriages, especially from Christians. The research method used is a literature study. The object of study is the giving of dowries in the marriages of Isaac and Rebekah, Jacob and Rachel, David and Michal, and Shechem and Dina. Theological reflections obtained from this study: First, dowry in the Bible is given as a sign of respect for women and their families. Second, dowry is not coercion but rather the ability of a man to prove his love for a woman who wants to be his wife. Therefore, if it is applied to the belis culture in the Sumbanese people, belis does not conflict with the Christian faith, and belis has positive things that aim to help each other. The implications include: First, belis must be given according to the man's ability. Second, belis may not be held to fulfill the personal ambitions of the bride and groom or their family. Purchase payments must be made for the common good. Third, belis is given in an honorable way. There is no need to justify any means to prove the ability to pay belis at high prices.